CITRA NYAI DALAM TIGA NOVEL INDONESIA - Jatmiko, Dheny (Universitas 17 Agustus 1945 Surabaya, 2020)
Nyai (the Javanese term for concubine) is one of the themes that is widely discussed in the realm of Indonesian literature starting from peranakan Chinese literature, literature during the colonial period, as well as modern Indonesian literature; both written by native writers and non-indigenous writers (Indonesians and peranakan Chinese). Based on these phenomena, this study will discuss the image of Nyai in literary works with a descriptive qualitative research method. The object materials of this research are the novels Nyai Wonokromo by Mayon Sutrisno, Tjerita Njai Isah by Ferdinand Wiggers, and Boenga Roos dari Tjikembang by Kwee Tek Hoay. In Nyai Wonokromo and Tjerita Njai Isah, the characters of Nyai presented in both novels are fool-blooded Dutch Nyai, while the novel Boenga Roos dari Tjikembang presents a Chinese Nyai. This study will compare the representation of Nyai as belonging to the Dutch and that of the Chinese, as well as comparing the images of Nyai written by indigenous writers and non-indigenous writers. The discussion of nyai includes the position of nyai in the social construction of society and its relationship with the people around it. Key words: nyai, women, colonial, peranakan Chinese, Europe